Hospital care for indigenous mexicans contaged initiating the COVID-19 pandemic - Horbath Corredor, Jorge (2022)
Identify the determinants of the change in the risk of hospitalization with and without and with intubation with respect to outpatient care in indigenous and non-indigenous patients according to conditions of indigenism with covid-19 at the beginning of the pandemic. With information from the Ministry of Health of Mexico on May 20, 2020, multinomial logistic models are developed for both groups of patients, adjusting for socioeconomic variables, health conditions and place of residence that show common conditions such as pneumonia and others, as well as residence in large cities for indigenous people due to their migration.